The erroneous interpretation of the registration Court on the disposition of assets with a book value of more than 50% of the share capital - Rey Bustamante, Alonso (2019)
The Registration Court has established that it is not necessary verify the previous existence of the agreement of the general meeting of shareholders for the acts in section 5 of article 115 of the General Corporation Law, because its execution is presumed.In this article, the authors examine what legal foundations are opposed to what the Court has established.